Electrophysiological mechanisms of action of the levorotatory isomer of sotalol in a canine infarct model of inducible ventricular tachycardia: comparison with the beta-1 receptor antagonist bisoprolol - Aidonidis, Isaac; Rizos, Ioannis-Antonios; Hilbel, Thomas; Kübler, Wolfgang; Brachmann, Johannes (Journal of molecular and cellular cardiology, 1994)
To evaluate the antiarrhythmic efficacy of I-sotalol and bisoprolol on inducible ventricular arrhythmias, conscious dogs with 4- to 8-day-old myocardial infarction were studied by programmed electrical stimulation. Direct recordings from infarcted and adjacent normal subepicardium were made using a specially designed composite electrode. From 18 dogs developing sustained ventricular tachycardia (sVT) during control stimulation. I-sotalol (1.5 mg/kg i.v.) prevented reinducibility of sVT in 10 animals, while in seven other animals it significantly reduced the rate of tachycardia. Bisoprolol (0.2 mg/kg i.v), tested in a separate group of 10 dogs susceptible to sVT, was mostly ineffective in preventing or slowing the tachycardia. Both agents significantly prolonged conduction time and refractoriness within the atrioventricular conduction system, and decreased heart rate. However, while I-sotalol lengthened ventricular refractoriness and QT interval, bisoprolol exerted only a minor effect on these parameters. Neither of the drugs affected conduction in normal and infarcted myocardium, as indicated by almost unchanged QRS complex width and duration of ventricular late potentials, respectively. The results indicate that acute beta-blockade is ineffective against sVT induced during the subacute stage of myocardial infarction. The antiarrhythmic efficacy of I-sotalol may predominantly be related to its prolonging effect on ventricular refractoriness, supporting the concept of pure class III action.
Elektronische Reproduktion der Druck-Ausgabe 25. Mai 2002
Gesehen am 27.05.2024